2007
DOI: 10.1177/096739110701500606
|View full text |Cite
|
Sign up to set email alerts
|

Curing Behaviour of Epoxy Resin with a Diamine Containing Heterocyclic Rings

Abstract: The curing behaviour of a new epoxy curing agent, 2, 6-di (p-aminophenyl) benzo[1.2.5.4] bisoxazole (DIABO) was discussed. Diglycidyl-4, 5-epoxycyclohexane -1,2-dicarboxylate (TDE) was cured with a mixture of DIABO and diaminodiphenylsulfone (DDS). The aspects investigated including the curing procedure, reaction kinetics parameters and the heat resistance of the product. Average apparent activation energy of the resin's curing reaction was 63.55 kJ/mol, calculated according to the Kissinger and the Ozawa meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Other than thermoplastics, CNTs are added to other polymers to improve the mechanical properties of engineering polymers such as epoxy resins. Among all the types of epoxies available, amine-cured epoxies are considered for the polymer matrix due to their superior engineering performance [ 78 , 79 ]. For example, Uthaman et al [ 80 ] found the addition of CNTs into the epoxy imparted an optimum increment in percentage by 52.9% (flexural strength) and 25.5% (flexural modulus), 29.5% (tensile strength) and 48.1% (tensile) with only 1.5 wt.% addition of CNTs.…”
Section: Mechanical Performance Of Cnts Reinforced Polymer Compositesmentioning
confidence: 99%
“…Other than thermoplastics, CNTs are added to other polymers to improve the mechanical properties of engineering polymers such as epoxy resins. Among all the types of epoxies available, amine-cured epoxies are considered for the polymer matrix due to their superior engineering performance [ 78 , 79 ]. For example, Uthaman et al [ 80 ] found the addition of CNTs into the epoxy imparted an optimum increment in percentage by 52.9% (flexural strength) and 25.5% (flexural modulus), 29.5% (tensile strength) and 48.1% (tensile) with only 1.5 wt.% addition of CNTs.…”
Section: Mechanical Performance Of Cnts Reinforced Polymer Compositesmentioning
confidence: 99%
“…CNTs can be added to polymers to improve the mechanical and thermal properties of engineering polymers, such as epoxy resin [ 4 , 5 ]. Generally, regarding the several types of epoxies available, amine-cured epoxies are considered for the polymer matrix in fiber reinforced composites due to their superior engineering performance [ 6 , 7 ]. Allaoui et al reported that the addition of CNTs enhanced the modulus and strength of the epoxy matrix [ 8 ].…”
Section: Introductionmentioning
confidence: 99%